Evaluation of faecal calprotectin as a valuable non-invasive marker in distinguishing gut pathogens in young children with acute gastroenteritis - Sýkora, Josef; Siala, Konrad; Huml, Michal; Varvařovská, Jana; Schwarz, Jan; Pomahačová, Renáta (Acta paediatrica (Oslo, Norway, 2010)
AIM: The aim of the study is to evaluate faecal calprotectin (f-CP) in children ≤3 years of age with acute gastroenteritis (AG) as an early predictor of bacterial inflammation. METHODS: We prospectively analysed f-CP levels and diagnostic workup in 107 consecutive children (66 AG, 41 controls). RESULTS: Children with bacterial AG (BAG) was found to have higher diarrheal frequency (p < 0.01), fever (p < 0.01), erythrocyte sedimentation rate (p < 0.001), white blood count (p < 0.01) and C-reactive protein (CRP) (p < 0.001) compared with viral AG (VAG). Vomiting was frequent in VAG (p < 0.001). f-CP negatively correlated with age in controls (r = -0.5998). BAG demonstrated significantly higher f-CP levels [median, 219 μg/g, interquartile range (IQR): 119-350.2] compared with VAG (49.3 μg/g, IQR: 8.8-131.1) as well as controls (26.5 μg/g, IQR: 14.9-55.1) (p < 0.001). VAG and control f-CP levels were similar. f-CP was the best-rated marker of BAG with a diagnostic accuracy of 92%. Receiver-operator characteristic analysis revealed an area under curve of 0.95 for identifying BAG; sensitivity and specificity of f-CP were 93% and 88%, respectively, at an adjusted cut-off point of 103.9 μg/g faeces. Combined f-CP and CRP yield improved diagnostic accuracy of 94% for BAG. CONCLUSION: f-CP facilitates early discrimination between bacterial and viral causes of AG in young children. Combining f-CP with CRP increases the diagnostic power of diagnosing BAG.
Keywords: virové nemoci; diferenciální diagnóza; Acute Disease; Female; feces; Feces; Infant; předškolní dítě; biologické markery; Biomarkers; ženské pohlaví; gastroenteritida; Bacterial Infections; lidé; Sensitivity and Specificity; studie případů a kontrol; senzitivita a specificita; leukocytární L1-antigenní komplex; Diagnosis, Differential; průjem; Virus Diseases; ROC křivka; Humans; prospektivní studie; Male; Case-Control Studies; kojenec; Prospective Studies; Diarrhea; Child, Preschool; akutní nemoc; Gastroenteritis; mužské pohlaví; Leukocyte L1 Antigen Complex; ROC Curve; bakteriální infekce